Measurement and modelling of salt and nutrient dynamics under Salicornia irrigated with saline groundwater, desalination reject-brine, and aquabrine : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Soil and Environmental Sciences, School of Agriculture and Environment, Massey University, Palmerston North, New Zealand - Al Tamimi, Mansoor (Massey University, 2024)
Environment Agency-Abu Dhabi (EAD) has implemented several scientific research projects with Plant and Food Research (PFR) New Zealand and OnlyFromNZ Limited (OFNZ) to determine the irrigation requirements for date palms, arid forestry, and field crops, for Law 5 which states that groundwater in the Emirate is the property of the Government which has the responsibility for management, organization and licensing the activities related to groundwater. The Government entity is EAD-Environment Agency of Abu Dhabi). can be implemented using sound scientific bases to protect the interests of all. This is a cooperation with external partners, plus both governmental and non-governmental agencies. These projects aimed to determine the irrigation requirements for date palms, forests, and field crops. While these projects have determined irrigation requirements, they have not, to date, addressed the environmental impacts of farming on groundwater quantity and quality. This Ph.D. research explored the trade-offs between improved technologies for the use of alternative water supplies, such as desalination brines, and the environmental consequences of brine re-use. The results will form part of the future solutions at the nexus among food, energy, and water in Abu Dhabi. This doctoral research builds on nearly a decade of scientific knowledge developed in collaboration with the New Zealand teams. It identifies the opportunities for reject brine from desalination units in aquaculture and halophytic agriculture, as well as the environmental consequences of the fate of this salt and nutrients. Measurements are critical to understand groundwater impacts and the benefits of using saline groundwater and brines from desalination plants to irrigate halophytes in hyper-arid environments. In 2020, a pilot trial was set up using irrigation with highly saline waters. However, two difficulties were encountered, and the pilot trial was a failure. The first part of the thesis describes how the practical challenges of the measurement technologies used in this saline environment were overcome. Further, experiments were then carried out to quantify the efficiency and impact of salt leaching in removing salt from the rootzone. Two years of field experimentation were undertaken to determine the economic productivity and environmental impact on groundwater of irrigating the halophyte Salicornia bigelovii with three types of saline waters in the hyper-arid United Arab Emirates. In the first year, the irrigation waters employed were groundwater (GW) at 25 dS m⁻¹, reverse-osmosis brine (RO) from a desalination unit at 40 dS m⁻¹, and Aquabrine (AQ) effluent from land-based aquaculture in tanks filled with RO brine, also at 40 dS m⁻¹. Bubblers (BUB), pressure-compensated drippers (PCD), or subsurface irrigation tape (SUB) were used to apply the three waters Salicornia fresh tip, harvest forage, and seed yields were highest for AQ applied through BUB, reaching 650 g m⁻². The dry forage yield with AQ through BUB was found to be 2-2.6 kg m⁻², compared to 1-2.3 kg m⁻² for the other irrigation waters and emitter devices. The highest water productivity WPI (kg m⁻³) across all three crop outputs resulted from Aquabrine applied by pressure-compensated drippers. Gross economic water productivity (GEWP₁, $ m⁻³) was assessed based solely on gross revenue. The highest GEWP₁, at US$5.8-6.2, was achieved with AQ applied through PCD and SUB, primarily due to revenue from fresh tips. Notably, the GEWP₁ significantly exceeded the cost of desalination at $1.5 m⁻³. Drainage and leaching were measured using fluxmeters. The greatest salt load into the groundwater, at 135-195 kg m⁻², was observed with BUB irrigation. For PCD and SUB, the salt load ranged between 14-36 kg m⁻². Simple mass-balance calculations of these salt loadings were then employed to predict the impact on the saline quality of aquifers. An exemplar loading of 75 kg m⁻² was used, resulting in a projected annual salinity rise of 2.6 dS m⁻¹ y⁻¹ for an aquifer with a saturated depth of 100 m. This significant increase in groundwater salinity would represent a continual decline in the resource's utility. This simple mass-balance arithmetic highlighted the need for modelling. New data from the following year’s experiments highlighted the economic value of using nitrogen-rich saline waters, either from groundwater or reject brines from desalination units, to irrigate the halophytic crop Salicornia bigelovii for food, fodder, and fuel in a hyper-arid environment. The greatest benefit was, again, achieved using pressure compensated drippers. Field measurements of drainage and leaching under the crop showed that, in sum, all of the salt, as well as the nitrogen drawn up from the groundwater were returned back to the aquifer as leachate. The only loss of water to the system was through crop evapotranspiration ET𝒸. A simple heuristic model of groundwater quantity and quality was developed to infer the environmental impacts of irrigating crops with saline and high-nitrate groundwater in a hyper-arid environment. The time-rise in solute concentration in groundwater is found to be a hyperbola. The parameters needed for this simple model are the fraction of the land above the aquifer that is irrigated, the initial depth of the saturated thickness of the aquifer, the saturated water content of the aquifer, and the annual rate of crop evapotranspiration. An indicator of the rate-of-rise in solute concentration, akin to a half-life, is the numbers of years to double the solute concentration in groundwater. This can be found as Ө hₒ /2 ET𝒸, where Ө is the saturated water content, hₒ is the original thickness of the saturated layer, and ET𝒸 is the annual rate of crop evapotranspiration. The general model is simple and straightforward to parameterise. It is easily understood and useful for assessing the impacts and trade-offs of policy and regulatory options. The knowledge gained from these experiments and the predictions resulting from the heuristic modelling have been used to highlight future needs to be addressed for the critical issues at the food-water-energy nexus in hyper-arid regions.
Keywords: exploring trade-offs of using alternative water supplies for agriculture in a hyper-arid environment; using different saline waters for irrigating a salt-tolerant crop; providing critical insights into the environmental impacts on groundwater; Horticulture; Arid regions; Salicornia; Irrigation; Salt-tolerant crops; Soils, Salts in; Groundwater; Abū Ẓaby (United Arab Emirates); 410601 Land capability and soil productivity; 300899 Horticultural production not elsewhere classified